PENERAPAN PEMBANGUNAN KARAKTER DI SEKOLAH DASAR: SUATU LITERATURE REVIEW - Ulfa, Lina Zumrotul; Ramadhani, Aqila Nur; Desmalasari, Shinta; Dewaningrum, Maulidia; Rianari, Evita Madani; Rofiki, Imam (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
Character education is a crucial aspect in the education system which aims to form individuals with strong moral and ethical values. The aim of this research is to determine the effect of implementing character development in elementary schools which has been analyzed from several previously researched scientific journals. The method used is a qualitative approach with a Literature Review. The results of this research are that character education can be integrated into the learning of every subject available in the curriculum. Character education functions to improve the quality of educational processes and outcomes which refer to the formation of character and noble morals for each student. Strengthening character education takes the form of understanding the concept of character education, socializing character education appropriately, creating a conducive school environment, providing supportive learning facilities, developing students' disciplinary attitudes and exemplary teachers for students. Based on research data that has been found, from fifteen studies there are thirteen research sources which state that research on the implementation of character education in elementary schools has been carried out well, while two of them have not been carried out well